Toward a Shared Vision for Cancer Genomic Data - Grossman, Robert L; Heath, Allison P; Ferretti, Vincent; Varmus, Harold E; Lowy, Douglas R; Kibbe, Warren A; Staudt, Louis M (The New England journal of medicine, 2016)
The Genomic Data Commons will initially house raw genomic data and diagnostic, histologic, and clinical outcome data from National Cancer Institute–funded projects. A harmonization process will align sequencing data to the genome and identify mutations and alterations. For the past 2 years, the National Cancer Institute (NCI), the University of Chicago, the Ontario Institute for Cancer Research, and Leidos Biomedical Research have been developing an information system called the NCI Genomic Data Commons (GDC) (see figure). The GDC will initially contain raw genomic data as well as diagnostic, histologic, and clinical outcome data from NCI-funded projects such as the Cancer Genome Atlas (TCGA) and the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) program. Unlike previous versions of these data sets, the genomic data will be “harmonized” using uniform analytic pipelines to align the raw sequencing data . . .